IMPACT OF MOTOR VEHICLES ON ATMOSPHERIC AIR. (World Bulletin of Public Health, 2023)
Protecting atmospheric air, which is the most important factor for human life, and ensuring its purity is one of the most urgent global problems today
Keywords: meteorological; components; transboundary; inert gases